Development of PPP-method realization for low earth orbit satellite trajectory determination using on-board gps-observations - Zhalilo, Alexey; Yakovchenko, Aleksander (Eastern-European Journal of Enterprise Technologies, 2016)
The results of development and testing of new PPP-method realization (Precise Point Positioning) for high-precision determination of Low Earth Orbit satellites (LEOS) trajectory parameters using the results of on-board GPS-observations and kinematic (geometric) positioning mode are presented. The peculiarities and features of the proposed variant of the PPP–method of GPS-observation processing with using of precise ephemerides and GPS satellites clocks as well as other information from the international IGS service and the French space agency CNES are described. The components of the observation error model and the results of “a priori” and “a posteriori” accuracy estimation of coordinate determinations are described. Using the example of on-board GPS-observations processing from specialized LEOS COSMIC it is indicated that for observation intervals of 30–40 minutes and more sub-decimeter accuracy of LEOS positioning may be achieved. The results of comparison of convergence of “float” and discrete/integer (“fixed”) methods of carrier-phase ambiguity resolution are presented. The presented development may be used for high-precision positioning and timing support of modern satellite technologies to detect contaminants, erosion studies, support of scientific and applied projects in geodesy, geophysics, climatology, orbitography, meteorology. The research results may be used in solving the problems of the LEOS maneuvering and docking.